Self-Efficacy of Social Science Education Teacher Candidates on Participating in Online Learning During the Covid-19 Pandemic - Indra Primahardani (STAI Hubbulwathan Duri, 2022)
This study describes and analyses the self-efficacy of students majoring in Social Science Education studying at various Teacher Training and Education Faculties in Pekanbaru Riau during online learning activities. The research design is a combination of quantitative and qualitative research to provide answers to the research questions. The research method is in the form of a survey with a non-experimental research approach. Therefore, the population of this study were all students majoring in social studies education at the three universities. Through Stratified Random Sampling Technique, 15% of active students at each university were selected as the samples. The instrument used is a questionnaire in a Google Form sent via WhatsApp. The responses given are arranged based on four levels of the Likert Scale. Based on data analysis, it can be concluded that the self-efficacy of Social Science Education students in Pekanbaru Riau during online learning is classified as good, with a response value of 50%.